Effects of Obesity on the Regulation of Macrophage Population in the Prostate Tumor Microenvironment. (3rd October 2017) - Galván, G. C.; Johnson, C. B.; Price, R. S.; Liss, M. A.; Jolly, C. A.; deGraffenried, L. A.
ABSTRACT: Obesity is associated with a greater risk of prostate cancer mortality. However, the mechanisms connecting obesity to the progression of prostate cancer remain unknown. This study determined the impact of obesity on macrophage recruitment and tumor-associated macrophage (TAM) polarization in the prostate tumor microenvironment, since a high concentration of TAMs in tumors has been linked to progression in prostate cancer. We utilized an in vitro model in which pre-adipocytes, prostate cancer cells, and macrophages were exposed to sera from obese or nonobese men, or conditioned media generated under obese or nonobese conditions. Matrigel invasion chambers were used to assess macrophage recruitment in vitro, and immunohistochemical analysis evaluated recruitment in a PTEN knockout mouse model. qPCR was used to measure mRNA levels of CCL2, COX-2, IL-10, TGF-beta, VEGF-A, arginase-1, and MMP-9. PGE2 production was measured by ELISA. Obesity increased macrophage and TAM recruitment, and increased mRNA levels of TAM markers in macrophages. Similarly, obese conditions increased CCL2 and COX-2 expression, as well as PGE2 levels in prostate cancer cells. COX-2 inhibition resulted in lower expression of obesity-induced TAM markers. Our data suggest that obesity promotes macrophage infiltration into the prostate tumor microenvironment, and induces TAM polarization through the COX-2/PGE2 pathway.